Method for synthesizing adiponitrile through selective ammoxidation of cyclohexene oxide

By using a heterophase vanadium-based catalyst to perform a one-step ammonia oxidation method in oxygen and ammonia atmosphere, the problems of iodine pollution and high cost in adiponitrile production in the prior art are solved, and a high yield, low energy consumption and environmentally friendly adiponitrile production process is achieved.

CN119707741AActive Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311267454.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The prior art has problems of iodine pollution, high cost and difficulty in industrial production in adipicnutrile production, and the production process of adipicnutrile has not yet developed a mature process.

Method used

Adipiconet was prepared by a one-step ammonia oxidation method in oxygen and ammonia atmosphere by a heterophase vanadium-based catalyst by epoxycyclohexane. The catalyst consists of CoaVbPcModMNOx/TiO2 and is prepared by impregnating a metal salt solution on anatase support, and the catalyst can be recycled.

Benefits of technology

The high yield of adiponitrile (84.8%) has been achieved, energy consumption and raw material costs have been reduced, pollution has been avoided, and the process route is short and investment is low, and it has the prospect of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a method for synthesizing adiponitrile through selective ammoxidation of cyclohexene oxide. The invention aims to simulate and optimize the process of synthesizing adiponitrile from cyclohexene oxide by a one-step direct ammoxidation method to develop a novel multiphase composite metal vanadium-based oxide catalyst, the composition of the catalyst is CoaVbPcModMNOx / TiO2, the active elements of the catalyst comprise vanadium element V, cobalt element Co, phosphorus element P and molybdenum element Mo, M is an auxiliary metal element (Mn, Cr, Fe or Ni), and N is an alkali metal (Na, K or Cs); the value range of a is 0.2 to 1.2; the value range of b is 0.8 to 1.5; the value range of c is 0.1 to 0.23; the value range of d is 0.07 to 0.35; x is the oxygen atom proportion required by the metal oxidation valence state. The catalyst has the advantages of simple preparation, good cycling stability, high yield and the like. The yield and the product purity of the adiponitrile are improved, the energy consumption in the production process of the adiponitrile is reduced, and the breakthrough of the production technology of the adiponitrile is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and application of selective ammonia oxidation catalysts, and specifically relates to a preparation method and application of a vanadium-based catalyst for synthesizing adiponitrile. Background Art

[0002] Adiponitrile is an intermediate of nylon 66 and the main raw material for producing hexamethylenediamine. Nylon 66, also known as polyhexamethylenediamine, is the main variety of polyamide plastics. It has a series of advantages such as high chemical stability, elasticity, strength, light resistance, water resistance, and high temperature resistance. Its main uses are: producing tire meridians, mechanical accessories such as gears and lubricating bearings, fishing nets, carpet yarns, nylon socks, swimwear, car seat belts, etc.; replacing non-ferrous metal materials as machine shells, car engine blades, etc. In today's rapidly developing automobile industry, nylon 66 cord fabric, as the main skeleton material of tires, is gradually becoming the most important post-processing product of adiponitrile. Its strength, life, and fatigue resistance are far superior to those of cord fabrics produced from rayon and polyester yarns, and it is also widely used in rubber conveyor belts, carpet yarns, engineering plastics, etc.

[0003] With the rapid development of nylon 66 industry in recent years, the demand for the raw material adiponitrile of the intermediate hexamethylenediamine has gradually increased. Adiponitrile accounts for about 45% of the production cost of nylon 66.

[0004] The production method of adiponitrile mainly includes four methods: acrylonitrile electrolytic dimerization method, adipic acid catalytic ammoniation method, caprolactam degradation and hydrolysis method and butadiene method. From the three aspects of technical advancement, product quality and production cost, the method of synthesizing adiponitrile by catalyzing cyclohexyl oxide with a one-step heterogeneous vanadium-based catalyst of the present invention is the most competitive and promising process technology route. At present, there is a document 1 that reports the route of preparing adiponitrile from cyclohexyl oxide, which is that cyclohexyl oxide can only obtain 70% adiponitrile yield under the action of 3.5 times of iodine when ammonia and acetonitrile are used as co-solvents. The above process has a large amount of iodine pollution, high cost and other problems, which are difficult to meet the requirements of industrial production. In comparison, in the presence of the vanadium-based catalyst, with cyclohexyl oxide as substrate, in an oxygen and ammonia atmosphere, with the addition of auxiliary agents, the adiponitrile yield is as high as 84.8%. Compared with the butadiene method and the iodine catalysis method, the adiponitrile synthesis technology proposed in the present invention has the advantages of using cheap multiphase metal catalysts and the catalysts can be recycled, low energy consumption for one-step reaction, low raw material cost, no pollution, high product quality and yield, short process route, relatively low investment, advanced technology, etc., and has great industrial application value.

[0005] [References]

[0006] 1.Ravindra R.Jadhav and Krishnacharya G.Akamanchi.*Chem.Lett.2013,42,162-164. Summary of the invention

[0007] The invention provides a novel heterogeneous vanadium-based catalyst for catalyzing a method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide.

[0008] According to the present invention, the method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide uses cyclohexene oxide as raw material, acetonitrile as solvent, oxygen and ammonia atmosphere, and under the action of a heterogeneous vanadium-based catalyst, the adiponitrile yield is as high as 84.8%.

[0009] According to the present invention, the multi-phase metal vanadium-based catalyst is a multi-component vanadium-based catalyst, which is composed of Co a V b P c Mo d MNOx / TiO 2 , the active elements include vanadium V, cobalt Co, phosphorus P and molybdenum Mo; M is an auxiliary metal element (Mn, Cr, Fe or Ni), and N is an alkali metal (Na, K or Cs);

[0010] The value range of a is 0.8~1.2;

[0011] The value range of b is 0.2~1.3;

[0012] The value range of c is 0.5~2.0;

[0013] The value range of d is 0.07 to 0.35;

[0014] x is the ratio of oxygen atoms required to satisfy the oxidation state of the metal.

[0015] According to the present invention, the multi-component multi-phase vanadium-based catalyst also includes an auxiliary metal M and an alkali metal N; the auxiliary metal element M is selected from one or more of manganese element Mn, chromium element Cr, iron element Fe and nickel element Ni, preferably a combination of Ni and Mn; the alkali metal element N is selected from one or more of sodium element Na, potassium element K and cesium element Cs, preferably K.

[0016] According to the present invention, the multi-component heterogeneous vanadium-based catalyst is prepared by impregnating a corresponding metal salt solution on an anatase carrier, and the specific steps are as follows:

[0017] 1) Dispersing or dissolving the required amount of carrier precursor and the corresponding metal salt precursor in an acidic solution with a mass concentration of 10-30%, stirring evenly, and aging at 40-80° C. for 12-48 hours to obtain solution A;

[0018] 2) Dissolve the vanadium precursor in the oxalic acid solution and stir at room temperature for 1 to 5 hours to obtain solution B.

[0019] 3) Adding solution B to solution A at the aging temperature and stirring to obtain a catalyst precursor solid, filtering, washing and drying; calcining at 300 to 800° C. in an oxygen atmosphere for 2 to 12 hours;

[0020] h obtains a multi-component heterogeneous vanadium-based catalyst product.

[0021] Wherein, the vanadium source is a vanadium compound, preferably a vanadium oxide;

[0022] The cobalt source is a cobalt compound, preferably a cobalt oxide;

[0023] The molybdenum source is a molybdenum compound, preferably a molybdenum oxide;

[0024] The phosphorus source is a phosphorus compound, preferably a soluble phosphate or phosphoric acid;

[0025] The molar ratio of the vanadium source, cobalt source, molybdenum source and phosphorus source is 1: (0.2-1.2): (0.05-0.25): (0.3-2.0), preferably 1: (0.4-1.0): (0.1-0.23): (0.5-1.6), and the molar amount of each metal raw material is calculated based on the molar amount of the element contained in the metal.

[0026] According to the present invention, the auxiliary metal element source is a salt or oxide containing nickel element Ni, manganese element Mn, iron element Fe and chromium element Cr, such as nickel chloride, manganese chloride, manganese oxide, ferric oxide, ferrous oxide, ferric chloride, ferrous chloride, chromium chloride, chromium oxide;

[0027] According to the present invention, the alkali metal element source is a soluble alkali metal salt, preferably an alkali metal hydrochloride, an alkali metal sulfate or an alkali metal nitrate; the molar ratio of the vanadium source, the auxiliary metal element source and the alkali metal element source is 1: (0.01-0.2): (0.02-0.35), preferably 1: (0.01-0.15): (0.04-0.25), and the molar amount of each metal raw material is calculated by the molar amount of the metal component element contained therein.

[0028] According to the present invention, the multi-component heterogeneous vanadium-based catalyst is a supported multi-component vanadium-based catalyst, and the catalyst carrier is selected from TiO 2 、CeO 2 、ZrO 2, Nb 2 O 5 、 2 O 5 、MgO、Al 2 O 3 、SiO 2 , hydroxyapatite, hydrotalcite, most preferably TiO 2 .

[0029] According to the present invention, the loading amount of the metal vanadium is one of 2wt%, 4wt%, 6wt%, 8wt% and 10wt%, and the most preferred amount is 4wt%.

[0030] According to the present invention, the reaction process of catalyzing the selective ammoxidation of cyclohexene oxide to synthesize adiponitrile is as follows:

[0031] Cyclohexene oxide (1 mmol), catalyst (50 mg), and acetonitrile (2 mL) were added to a 10 mL reaction tube in sequence, and then the reaction tube was placed in a high-pressure reactor, which was sealed; a certain amount of oxygen was filled in for replacement three times, and a leak test was performed, and then 0.5 MPa O 2 and 0.5MPa NH 3 , placed in an 80℃ oil bath, stirred at 550r / min for 12h; after the reaction, the reactor was naturally cooled to room temperature, the air was slowly released and the pressure was reduced, 20mg of naphthalene was added as an internal standard, and then 2mL of methanol was added for dilution, stirred, ultrasonicated, mixed evenly, centrifuged, and the supernatant was taken for GC / GC-MS analysis.

[0032] According to the present invention, in the method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide, the catalytic performance is related to the amount of catalyst used. Too low an amount will affect the activity of the catalytic reaction, and too high an amount will increase the cost of the catalyst; therefore, an appropriate amount needs to be selected. In order to ensure the activity of the catalyst and reduce the cost of the catalyst, the molar ratio of the V content in the catalyst used to the substrate is in the range of 1 to 10 mol%, and the preferred molar ratio is in the range of 2 to 5 mol%.

[0033] According to the present invention, the method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide, the reaction solvent is any one of toluene, acetonitrile, tert-amyl alcohol, 1,2-dichloroethane, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), n-heptane, tetrahydrofuran, and water, and acetonitrile is most preferred.

[0034] According to the present invention, the method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide, the reaction temperature used is 60-120°C; the reaction time is 4-24h; the most preferred reaction temperature is 80-100°C, and the most preferred reaction time is 10-16h. The product obtained after the reaction is adiponitrile, and the product yield and selectivity are determined by chromatographic internal standard method.

[0035] According to the present invention, the method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide is a heterogeneous catalytic system, and the heterogeneous vanadium-based catalyst can be recycled for more than 8 cycles without significant reduction in activity.

[0036] According to the present invention, the substrate is scaled up to kilogram level, and under standard conditions, the selectivity of adiponitrile can reach 84.8% after 12 hours of reaction. The scaled-up experimental results prove the potential application value of the reaction system.

[0037] This method has high catalytic oxidation efficiency, good selectivity, and high product yield. It not only greatly improves the atomic utilization rate, but is also economical and environmentally friendly, and has good application prospects.

[0038] The catalyst has the advantages of simple preparation, good cycle stability, high yield, etc. It can improve the yield and product purity of adiponitrile, reduce the energy consumption of adiponitrile production process, and achieve a breakthrough in adiponitrile production technology.

[0039] Compared with the prior art, the present invention has the following advantages and effects:

[0040] (1) The raw materials required for the preparation of the multi-phase cheap vanadium-based catalyst used in the present invention are simple and easy to obtain, and the preparation conditions are simple, so it is very easy to synthesize in large quantities. The catalyst has a good recycling effect. After the reaction, it can be reused after simple filtration, washing and drying, and the catalytic activity and selectivity are not changed.

[0041] (2) The present invention is completely different from the existing foreign butadiene technology (as shown in Formula 1), and is a completely new process route: starting from cyclohexene oxide, a one-pot ammoxidation method is used to directly prepare adiponitrile. Compared with the butadiene method, this route has the advantages of one-step reaction, using a recyclable multiphase cheap metal catalyst, and not using hydrocyanic acid. The yield of adiponitrile in this route can reach 84.8%, and the route is simple, green and pollution-free, and has a better prospect for industrial production.

[0042]

[0043] (3) Compared with other existing production processes (as shown in Table 1), the electrolytic production process of acrylonitrile has a wide range of raw materials, low energy consumption, high yield and high product quality. However, due to the high market price of acrylonitrile and the small production scale, it has been gradually eliminated; the butadiene method has a complex production process, serious corrosion equipment, large investment and a large amount of hydrocyanic acid consumption, and has been basically eliminated. The direct cyanidation method has the characteristics of low raw material cost, no pollution, high product quality and yield, short process route, relatively low investment, etc., and has advanced technology. No mature process has been developed in China; the catalytic amination method of adipic acid has been basically eliminated due to the high cost of adipic acid.

[0044] In summary, there is no mature process for the production of adiponitrile in China, so the production of adiponitrile has become one of the key factors restricting the development of my country's nylon 66 industry. By comparing the industrialized adiponitrile production process routes in the world and based on the current raw material market situation, it is believed that the one-step ammoxidation of cyclohexene oxide has the advantages of novel and reliable process, low cost, low pollution, recyclable catalyst, high product quality and high yield, and is currently the focus of the development of adiponitrile production process in my country.

[0045] Table 2 Comparison of adiponitrile production processes

[0046] project Acrylonitrile method Adipic acid method Butadiene method One-step ammonia oxidation Source of raw materials widely widely widely widely Raw material cost high high generally Low Process generally complex generally Simple Energy consumption high generally Lower Low Scale production Small scale Moderate size Large scale Large scale Product Quality generally generally generally high Yield Lower Lower Higher high Environmental friendly High pollution Pollution in general Pollution in general Low pollution invest Higher Lower Lower Lower DETAILED DESCRIPTION

[0047] The following examples will help to understand the present invention, but the present invention is not limited thereto.

[0048] Example 1

[0049] Preparation of catalyst: Co a V b P c Mo d Ox / TiO 2

[0050] The multi-component heterogeneous vanadium-based catalyst is prepared by impregnating a corresponding metal salt solution on an anatase carrier, and the specific steps are as follows:

[0051] 1) Dispersing or dissolving the required amount of carrier precursor and the corresponding metal salt precursor in an acidic solution with a mass concentration of 10-30%, stirring evenly, and aging at 40-80° C. for 12-48 hours to obtain solution A;

[0052] 2) Dissolve the vanadium precursor in the oxalic acid solution and stir at room temperature for 1 to 5 hours to obtain solution B.

[0053] 3) adding solution B to solution A at the aging temperature and under stirring to obtain a catalyst precursor, spraying and drying; and calcining at 300-800° C. in an oxygen atmosphere for 2-12 hours to obtain a multi-component heterogeneous vanadium-based catalyst product.

[0054] Wherein, the vanadium source is a vanadium compound, preferably a vanadium oxide;

[0055] The cobalt source is a cobalt compound, preferably a cobalt oxide;

[0056] The molybdenum source is a molybdenum compound, preferably a molybdenum oxide;

[0057] The phosphorus source is a phosphorus compound, preferably a soluble phosphate or phosphoric acid;

[0058] The molar ratio of the vanadium source, cobalt source, molybdenum source and phosphorus source is 1: (0.2-1.2): (0.05-0.25): (0.3-2.0), preferably 1: (0.4-1.0): (0.1-0.23): (0.5-1.6), and the molar amount of each metal raw material is calculated based on the molar amount of the element contained in the metal.

[0059] Example 2

[0060] Cyclohexene oxide (1 mmol), catalyst (50 mg), and acetonitrile (2 mL) were added to a 10 mL reaction tube in sequence, and then the reaction tube was placed in a high-pressure reactor, which was sealed; oxygen was filled into the reactor to replace the atmosphere three times, and a leak test was performed, and then 0.5 MPa O 2 and 0.5MPa NH 3 , placed in an 80℃ oil bath, stirred at 550r / min for 12h; after the reaction, the reactor was naturally cooled to room temperature, the air was slowly released and the pressure was reduced, 20mg of naphthalene was added as an internal standard, and then 2mL of methanol was added for dilution, stirred, ultrasonicated, mixed evenly, centrifuged, and the supernatant was taken for GC / GC-MS analysis.

[0061] Example 3

[0062] Catalyst A (4wt%Co 0.4 VP 0.5 Mo 0.1 Ni 0.01 K 0.04 O 2.69 / TiO 2 )

[0063] Dissolve 36g of vanadium pentoxide and 13g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 23g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 7.8g of ammonium molybdate, stir for 2 hours. After stirring, add 0.513g of nickel chloride and 1.18g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1: 0.4: 0.5: 0.1: 0.01: 0.04.

[0064] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, sprayed and dried to obtain a catalyst precursor. The catalyst was taken out and placed in a muffle furnace, programmed to 600°C, calcined for 12 hours, and cooled to room temperature to obtain a titanium dioxide-supported vanadium-based catalyst A (wherein 4wt% is the percentage of vanadium element relative to the carrier), which was bottled for later use.

[0065] Example 4

[0066] Catalyst B (4wt%CoVP 1.6 Mo 0.23 Ni 0.15 K 0.25 O 2.72 / TiO 2 )

[0067] Dissolve 36g of vanadium pentoxide and 32.8g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 73g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 17.8g of ammonium molybdate, stir for 2 hours. After stirring, add 7.7g of nickel chloride and 7.4g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1: 1.6: 0.23: 0.15: 0.25.

[0068] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, sprayed and dried to obtain a catalyst precursor. The catalyst was taken out and placed in a muffle furnace, programmed to 600°C, calcined for 12 hours, and cooled to room temperature to obtain a titanium dioxide-supported vanadium-based catalyst B (wherein 4wt% is the percentage of vanadium element relative to the carrier), which was bottled for later use.

[0069] Example 5

[0070] Catalyst C (4wt%Co 0.4 VP 0.5 Mo 0.1 Mn 0.01 K 0.04 O2.69 / TiO 2 )

[0071] Dissolve 36g of vanadium pentoxide and 13g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 23g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 7.8g of ammonium molybdate, stir for 2 hours. After stirring, add 0.67g of monohydrated manganese sulfate and 1.18g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1: 0.4: 0.5: 0.1: 0.01: 0.04.

[0072] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, sprayed and dried to obtain a catalyst precursor. The catalyst was taken out and placed in a muffle furnace, heated to 600°C, and calcined for 12 hours. After cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst C (4wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

[0073] Example 6

[0074] Catalyst D (4wt%CoVP 1.6 Mo 0.23 Mn 0.15 K 0.25 O 2.72 / TiO 2 )

[0075] Dissolve 36g of vanadium pentoxide and 32.8g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 73g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 17.8g of ammonium molybdate, stir for 2 hours. After stirring, add 10g of monohydrated manganese sulfate and 7.4g of potassium chloride, stir for 3 hours. The molar ratio of the added metal elements is V: Co: P: Mo: Ni: K = 1: 1: 1.6: 0.23: 0.15: 0.25.

[0076] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, sprayed and dried to obtain a catalyst precursor. The catalyst was taken out and placed in a muffle furnace, programmed to 600°C, calcined for 12 hours, and cooled to room temperature to obtain a titanium dioxide-supported vanadium-based catalyst D (wherein 4wt% is the percentage of vanadium element relative to the carrier), which was bottled for later use.

[0077] Example 7

[0078] Catalyst E (4wt% Co 0.8 VP1.2 Mo 0.15 Ni 0.05 K 0.14 O 2.52 / TiO 2 , abbreviated as 4wt%VOx / TiO 2 )

[0079] Dissolve 36g of vanadium pentoxide and 26.3g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 54.8g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6g of ammonium molybdate, stir for 2 hours. After stirring, add 2.57g of nickel chloride and 4.13g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1: 0.8: 1.2: 0.15: 0.05: 0.14. (4wt% is the percentage of vanadium element relative to the carrier)

[0080] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, sprayed and dried to obtain a catalyst precursor. The catalyst was taken out and placed in a muffle furnace, heated to 600°C, and calcined for 12 hours. After cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst E (4wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

[0081] Examples 8-12

[0082] The process and conditions are the same as in Example 7, except that the amount of carrier added is different, the catalyst (2wt%, 6wt%, 8wt%, 10wt%, 50wt% Co 0.8 VP 1.2 Mo 0.15 Ni 0.05 K 0.14 Ox / TiO 2 )

[0083] The titanium dioxide supported vanadium-based catalyst was prepared according to the method of Example 7, with the only difference being: the amount of vanadium element loaded relative to the carrier (where 2wt%, 6wt%, 8wt%, 10wt%, and 50wt% are the percentages of vanadium element relative to the carrier). 50wt%VOx / TiO 2 (i.e. the mass ratio of vanadium element to carrier is 1:1);

[0084] Examples 13-19

[0085] The titanium dioxide supported vanadium-based catalyst was prepared according to the method of Example 3. The process and conditions were the same as those of Example 3, and the only difference was that the type of carrier was different.

[0086] Among them, the carrier may be CeO 2 、ZrO 2 , Nb 2 O 5 、 2 O 5 、MgO、Al 2 O 3 、SiO 2 One of them, VOx / CeO 2、 VOx / ZrO 2 、VOx / Nb 2 O 5 、VOx / Ta 2 O 5 、VOx / MgO、VOx / Al 2 O 3 、VOx / SiO 2 .

[0087] Embodiment 20

[0088] Except for the different types of catalyst carriers and the loading amount of vanadium, the evaluation of catalyst activity was the same as in Example 2. The reaction conditions and catalytic reaction results are shown in Table 1. It can be seen from Table 1 that: 1) the type and doping ratio of metal may have a certain influence on the catalytic activity (Examples 3-6); different selections of catalyst carriers may lead to different final catalytic performances, among which TiO 2 The catalytic activity is the highest when used as a carrier (Examples 13-19); different V element loadings may lead to different catalytic activities, among which the catalytic activity is the highest when the V loading is 4wt% (Examples 7-12);

[0089] In conclusion, the type of catalyst carrier, the doping ratio of elements, the loading amount of vanadium, the reaction temperature, and the reaction time will all affect the efficiency of the catalytic ammoxidation of cyclohexene oxide to adiponitrile.

[0090]

[0091] Table 1 Condition screening of selective ammoxidation of cyclohexene oxide to adiponitrile

[0092] catalyst Conversion(%) Selectivity(%) Yield(%) Example 3 Catalyst A 100 60.8 60.8 Example 4 Catalyst B 100 77.7 77.7 Example 5 Catalyst C 100 75.3 75.3 Example 6 Catalyst D 100 83.7 83.7 Example 7 Catalyst E 100 84.8 84.8 Example 8 <![CDATA[2wt%VOx / TiO 2 ]]> 96 78.4 75.3 Example 9 <![CDATA[6wt%VOx / TiO 2 ]]> 100 80.3 80.3 Example 10 <![CDATA[8wt%VOx / TiO 2 ]]> 100 78.9 78.9 Embodiment 11 <![CDATA[10wt%VOx / TiO 2 ]]> 94 74.5 70 Example 12 <![CDATA[VOx / TiO 2 (1:1)]]> 93 80.6 75 Embodiment 13 <![CDATA[VOx / CeO 2 ]]> 90 67 60.3 Embodiment 14 <![CDATA[VOx / ZrO 2 ]]> 92 73.4 67.5 Embodiment 15 <![CDATA[VOx / Nb 2 THE 5 ]]> 77 81.8 63 Example 16 <![CDATA[VOx / Ta 2 THE 5 ]]> 89 57.1 50.8 Embodiment 17 VOx / MgO 70 45.3 31.7 Embodiment 18 <![CDATA[VOx / Al 2 THE 3 ]]> 84 64.4 54.1 Embodiment 19 <![CDATA[VOx / SiO 2 ]]> 100 55 55

[0093] Comparative Example 1

[0094] 2wt%VOx / TiO 2 Preparation

[0095] Dissolve 18g of vanadium pentoxide and 26.3g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 54.8g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6g of ammonium molybdate, stir for 2 hours. After stirring, add 2.57g of nickel chloride and 4.13g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 0.5: 0.8: 1.2: 0.15: 0.05: 0.14. (2wt% is the percentage of vanadium element relative to the carrier)

[0096] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, filtered, washed with spray, and dried to obtain a catalyst precursor. The catalyst precursor was taken out and placed in a muffle furnace, heated to 600°C, and calcined for 12 hours. After cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst E (2wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

[0097] Comparative Example 2

[0098] Catalyst E (4wt% Co 0.8 VP 1.2 Mo 0.15 Ni 0.05 K 0.14 O 2.52 / TiO 2 , abbreviated as 4wt%VOx / TiO 2 )

[0099] Dissolve 36g of vanadium pentoxide and 26.3g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 54.8g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6g of ammonium molybdate, stir for 2 hours. After stirring, add 2.57g of nickel chloride and 4.13g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1: 0.8: 1.2: 0.15: 0.05: 0.14. (4wt% is the percentage of vanadium element relative to the carrier)

[0100] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, filtered, washed and sprayed, and dried to obtain a catalyst precursor. The catalyst precursor was taken out and placed in a muffle furnace, heated to 600°C, and calcined for 12 hours. After cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst E (4wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

[0101] Comparative Example 3

[0102] 6wt%VOx / TiO 2 Preparation

[0103] Dissolve 54g of vanadium pentoxide and 26.3g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 54.8g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6g of ammonium molybdate, stir for 2 hours. After stirring, add 2.57g of nickel chloride and 4.13g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1.5: 0.8: 1.2: 0.15: 0.05: 0.14. (6wt% is the percentage of vanadium element relative to the carrier)

[0104] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, filtered, washed and sprayed, and dried to obtain a catalyst precursor. The catalyst precursor was taken out and placed in a muffle furnace, heated to 600°C, and calcined for 12 hours. After cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst E (6wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

[0105] Comparative Example 4

[0106] 8wt%VOx / TiO 2 Preparation

[0107] Dissolve 72g of vanadium pentoxide and 26.3g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 54.8g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6g of ammonium molybdate, stir for 2 hours. After stirring, add 2.57g of nickel chloride and 4.13g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 2: 0.8: 1.2: 0.15: 0.05: 0.14. (8wt% is the percentage of vanadium element relative to the carrier)

[0108] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, filtered, washed with spray, and dried to obtain a catalyst precursor. The catalyst precursor was taken out and placed in a muffle furnace, heated to 600°C, and calcined for 12 hours. After cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst E (8wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

[0109] Comparative Example 5

[0110] 10wt%VOx / TiO 2 Preparation

[0111] Dissolve 90g of vanadium pentoxide and 26.3g of cobalt trioxide in 500mL of 100g of oxalic acid aqueous solution, add 54.8g of 85wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6g of ammonium molybdate, stir for 2 hours. After stirring, add 2.57g of nickel chloride and 4.13g of potassium chloride, stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 2.5: 0.8: 1.2: 0.15: 0.05: 0.14. (10wt% is the percentage of vanadium element relative to the carrier)

[0112] The support anatase (TiO 2 ) was added to the above solution, stirred evenly, immersed at 40°C for 48 hours, filtered, washed with spray, and dried to obtain a catalyst precursor. The catalyst precursor was taken out and placed in a muffle furnace, programmed to 600°C, calcined for 12 hours, and cooled to room temperature to obtain a titanium dioxide-supported vanadium-based catalyst E (wherein 10wt% is the percentage of vanadium element relative to the carrier), which was bottled for later use.

[0113] It can be seen from the above embodiments and comparative examples that the multiphase composite metal catalyst used in the present invention has a simple metal composition, good fluidization, strong water resistance, wear resistance, strong cycle stability, and has great industrial application value.

[0114] The one-step ammoxidation method of epoxycyclohexane of the present invention has the advantages of novel and reliable process, low cost, low pollution, recoverable catalyst, high product quality and high yield, and is the focus of the current development of adiponitrile production process in my country. The yield of adiponitrile can reach 84.8%, the route is simple, green and pollution-free, and has the prospect of industrial production.

Claims

1. A method for synthesizing adiponitrile by selective ammoxidation of cyclohexene oxide, characterized in that: Using cyclohexene oxide as raw material, acetonitrile as solvent, oxygen and ammonia atmosphere, and under the action of heterogeneous metal vanadium-based catalyst, cyclohexene oxide is selectively ammoxidized to synthesize adiponitrile; The multi-phase metal vanadium-based catalyst is a multi-component vanadium-based catalyst, wherein the active elements include vanadium element V, cobalt element Co, phosphorus element P and molybdenum element Mo; The molar ratio of vanadium, cobalt, molybdenum and phosphorus is 1: (0.2-1.2): (0.05-0.25): (0.3-2.0), preferably 1: (0.4-1.0): (0.1-0.23): (0.5-1.6), and more preferably 1: (0.5-0.8): (0.12-0.21): (0.6-1.5).

2. The method according to claim 1, characterized in that: The multi-component heterogeneous vanadium-based catalyst further comprises one or more of auxiliary metals M or alkali metals N; The auxiliary metal element M is selected from one or more of manganese element Mn, chromium element Cr, iron element Fe and nickel element Ni, preferably a combination of Ni and Mn, with a molar ratio ranging from 1: (0.1 to 1.2), preferably ranging from 1: (0.5 to 1.0); The alkali metal element N is selected from one or more of sodium element Na, potassium element K and cesium element Cs, preferably K; The molar ratio of vanadium, auxiliary metal element M and alkali metal N is 1: (0.01-0.2): (0.02-0.35), preferably 1: (0.01-0.15): (0.04-0.25), more preferably 1: (0.02-0.14): (0.05-0.24); The active element and the auxiliary metal M are present in the catalyst in the form of oxides, respectively, and the alkali metal N is present in the catalyst in the form of a complex cation.

3. The method according to claim 1 or 2, characterized in that: Catalyst E (2~50 wt% Co 0.8 VP 1.2 Mo 0.15 Ni 0.05 K 0.14 O 2.52 / TiO2, abbreviated as 2~50 wt% VOx / TiO2): Dissolve 36 g of vanadium pentoxide and 26.3 g of cobalt trioxide in 500 mL of 100 g of oxalic acid aqueous solution, add 54.8 g of 85 wt% phosphoric acid solution, stir for 2 hours, then slowly add 11.6 g of ammonium molybdate and stir for 2 hours. After stirring, add 2.57 g of nickel chloride and 4.13 g of potassium chloride and stir for 3 hours. The molar ratio of each metal element added is V: Co: P: Mo: Ni: K = 1: 0.8: 1.2: 0.15: 0.05: 0.

14. (wt% is the percentage of vanadium element relative to the carrier) Add the carrier anatase (TiO2) to the above solution, stir evenly, and heat for 40-60 o After immersion for 48 hours, the catalyst precursor was filtered, washed and dried. The catalyst precursor was placed in a muffle furnace and heated to 500-800 °C. o C, calcined for 6 to 12 hours, and after cooling to room temperature, a titanium dioxide-supported vanadium-based catalyst E (wherein wt% is the percentage of vanadium element relative to the carrier) was obtained, which was bottled for later use.

4. The method according to claim 1 or 2, characterized in that: The multi-component heterogeneous vanadium-based catalyst is a supported catalyst, and the catalyst carrier is selected from one or more of TiO2, CeO2, ZrO2, Nb2O5, Ta2O5, MgO, Al2O3, SiO2, hydroxyapatite, and hydrotalcite, preferably TiO2, and most preferably anatase TiO2; The mass loading amount of the metal vanadium relative to the carrier is 2wt%-50%, preferably 2wt%-10wt%, and most preferably 3wt%-5wt%.

5. The method according to claim 1, 2 or 3, characterized in that: The multi-phase metal vanadium-based catalyst is a multi-component vanadium-based catalyst, which consists of Co a V b P c Mo d MNOx / TiO2, whose active elements include vanadium V, cobalt Co, phosphorus P and molybdenum Mo; M is an auxiliary metal element (one or more of Mn, Cr, Fe or Ni), and N is an alkali metal (one or more of Na, K or Cs); The value range of a is 0.2~1.2; The value range of b is 0.8~1.5; The value range of c is 0.1~2.0; The value range of d is 0.07~0.35; Wherein, a, b, c or d refers to the molar ratio; x is the ratio of oxygen atoms required to satisfy the metal oxidation state; The metal oxidation states are: The oxidation state of cobalt Co may be one or more of +2 or +3; The oxidation state of vanadium V may be one or more of +2, +3, +4 or +5; The oxidation state of molybdenum Mo may be one or more of +4 or +6; The oxidation state of manganese Mn may be one or more of +2, +3, +4, +5, +6 or +7; The oxidation state of chromium Cr may be one or more of +2, +3 or +6; The oxidation state of iron Fe may be one or more of +2, +3, +4, +5 or +6; The oxidation state of nickel Ni may be one or more of +1, +2, +3 or +4.

6. The method according to any one of claims 1 to 5, characterized in that: The multi-component heterogeneous vanadium-based catalyst is prepared by impregnating a corresponding metal salt solution on a carrier, and the specific steps are as follows: 1) Disperse or dissolve the required amount of carrier precursor and the corresponding metal salt precursor in an acidic solution with a mass concentration of 10-30%, stir evenly, and heat at 40-80 o C for 12-48 h to obtain solution A; 2) Dissolve the vanadium precursor in oxalic acid solution and stir at room temperature for 1 to 5 h to obtain solution B; 3) Add solution B to solution A under aging temperature and stirring to obtain catalyst precursor, spray and dry; o C was calcined at high temperature for 2 to 12 h in an oxygen atmosphere to obtain a multi-component heterogeneous vanadium-based catalyst product; Wherein, the vanadium source is a vanadium compound, preferably a vanadium oxide; The cobalt source is a cobalt compound, preferably a cobalt oxide; The molybdenum source is a molybdenum compound, preferably a molybdenum oxide; The phosphorus source is a phosphorus compound, preferably one or more of soluble phosphates or phosphoric acid; The molar ratio of the vanadium source, cobalt source, molybdenum source and phosphorus source is 1: (0.2-1.2): (0.05-0.25): (0.3-2.0), preferably 1: (0.4-1.0): (0.1-0.23): (0.5-1.6), and the molar amount of each metal raw material is calculated based on the molar amount of the element contained in the metal.

7. The method according to claim 6, characterized in that: The auxiliary metal element source is one or more salts or oxides containing one or more of nickel element Ni, manganese element Mn, iron element Fe and chromium element Cr, such as one or more of nickel chloride, manganese chloride, manganese oxide, ferric oxide, ferrous oxide, ferric chloride, ferrous chloride, chromium chloride and chromium oxide; The alkali metal element source is a soluble alkali metal salt, preferably one or more of alkali metal hydrochlorides, alkali metal sulfates or alkali metal nitrates; the molar ratio of the vanadium source, the auxiliary metal element source and the alkali metal element source is 1: (0.01-0.2): (0.02-0.35), preferably 1: (0.01-0.15): (0.04-0.25), and the molar amount of each metal raw material is calculated based on the molar amount of the metal component element contained therein.

8. According to any one of claims 1 to 7, the reaction process of catalyzing the selective ammoxidation of cyclohexene oxide to synthesize adiponitrile is as follows: Add cyclohexene oxide (1 mmol), catalyst (20-80 mg, preferably 40-60 mg), and reaction solvent (1-5 mL, preferably 1-3 mL) into a sealed high-pressure reactor, respectively; then fill with 0.5 MPa O2 and 0.5 MPa NH3, respectively, place in an oil bath at 60-120 °C (preferably 80-100 °C), stir and react for 4-24 h (preferably 10-16 h) to obtain the target product.

9. The method according to claim 8, characterized in that: The reaction solvent is any one or more of toluene, acetonitrile, tert-amyl alcohol, 1,2-dichloroethane, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), n-heptane, tetrahydrofuran, and water, and acetonitrile is most preferred.

10. The method according to claim 8, characterized in that: The molar ratio of V content in the catalyst used to the substrate is in the range of 1-10 mol%, and the preferred molar ratio is in the range of 2-5 mol%.

Citation Information

Patent Citations

  • Method for oxidation synthesis of adipic acid by epoxy cyclohexane

    CN101177390A

  • A continuous preparation method for 1,2-cyclohexanediamine

    CN109553538A

  • Method for preparing adiponitrile by catalytic ammonia oxidation cracking of cyclohexanol

    CN109956888A

  • Vanadium catalyst and method for catalytically synthesizing adiponitrile by using vanadium catalyst

    CN115990498A

  • Process for vapor phase ammoxidation

    US3845094A

Cited By

  • Method for preparing adiponitrile by catalyzing cyclohexanone through phosphorus-nitrogen co-doped porous carbon / CoP composite material

    CN120757467A

  • Method for preparing adiponitrile through ammoxidation of cyclohexene

    CN121159424A

  • Process for the preparation of adiponitrile by cyclohexene ammoxidation

    CN121159424B

  • A method for the oxidation of hexanedial to prepare adiponitrile

    CN122668037A